2009
DOI: 10.4049/jimmunol.0900666
|View full text |Cite
|
Sign up to set email alerts
|

Analogous Interactions in Initiating Complexes of the Classical and Lectin Pathways of Complement

Abstract: The classical and lectin pathways of complement activation neutralise pathogens and stimulate key immunological processes. Both pathways are initiated by collagen-containing, soluble pattern-recognition molecules associated with specific serine proteases. In the classical pathway, C1q binds to antibody-antigen complexes or bacterial surfaces to activate C1r and C1s. In the lectin pathway, mannan-binding lectin (MBL) and ficolins bind to carbohydrates on pathogens to activate MASP-2. To characterise the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
59
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 50 publications
(83 reference statements)
10
59
2
Order By: Relevance
“…The structure is compatible with previous mutagenesis data that highlight the importance of the lysine residue in the collagen and Glu45 and Asp98 in C1s, and explains the Ca 2+ dependence of binding (11,12). It shares a number of similarities with the complex between the CUB2 domain of MASP-1 bound to a collagen-like peptide of MBL of the lectin pathway (15).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The structure is compatible with previous mutagenesis data that highlight the importance of the lysine residue in the collagen and Glu45 and Asp98 in C1s, and explains the Ca 2+ dependence of binding (11,12). It shares a number of similarities with the complex between the CUB2 domain of MASP-1 bound to a collagen-like peptide of MBL of the lectin pathway (15).…”
Section: Resultssupporting
confidence: 87%
“…In addition, there is overall charge complementarity, with the binding regions of CUB1 and CUB2 having net negative and positive charges, respectively. A C1s-C1s interaction at the center of the C1 complex has been predicted in previous molecular dynamics and modeling studies (11,12,17) but has not been observed directly. In the absence of C1q, the interaction must be weak because only C1s dimers are detected in solution (corresponding to the X-shaped dimers), but is stabilized when C1r-C1s tetramers bind to C1q, explaining how the elongated proteases form the compact structures observed in electron micrographs of the C1 complex (9).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Three MASPs have been identified, MASP-1, MASP-2, and MASP-3, among which only MASP-1 and MASP-2 are essential for complement activation (7), whereas the role of MASP-3 still requires further elucidation. The three MASPs and the C1s-C1r-C1r-C1s tetramer interact in a similar way with the collagen-like stalks of the recognition proteins, which allows in vitro cross-interaction between subcomponents of the classical and lectin pathways (8,9). Following recognition of a target, the activated C1 and MBL/ficolin-MASP proteolytic complexes cleave complement components C4 and C2 to generate the C3 convertase responsible for cleavage of C3 and subsequent opsonization of the target by C3 fragments such as C3b.…”
mentioning
confidence: 99%